Perancangan tempat sampah otomatis berbasis arduino - Daffa Rizki Putra Noordi; Irfan Agus Prastowo; Muhammad Aqsha Rizki Sugiarto; Dwi Hartanti (ARKA INSTITUTE, 2022)
Trash cans that have been provided by cleaning agencies only become silent decorations on the streets that are not taken care of and not attractive. Maybe it is also a factor that causes humans to be reluctant to throw garbage. Reflecting on this, each individual's awareness of environmental cleanliness is needed and further improved to minimize the waste that scatters on the streets. In raising awareness of concern for environmental cleanliness, Sometimes it requires a unique way for each individual to be interested, so do not hesitate to throw garbage in its place. The purpose of this research is to produce a tool that is a unique and interesting trash can, Can open and close automatically if any movement is detected. So it is expected that the tool is able to attract attention so that people can throw garbage in its place. This research is carried out based on the results of data collection analysis, direct observation of the system how the tool works, interviews with related parties.